The safety and efficacy of the Mo.Ma system device for carotid artery stenting: A single-center experience from Taiwan - Cheng, Cheng-Chung; Lin, Chin-Sheng; Yin, Wei-Hsian; Lin, Chin; Liu, I-Fan; Lee, Yu-Feng; Liu, Wei-Ting; Fu, Hao-Neng; Huang, Chien-Lung; Tsao, Tien-Ping (Frontiers in Cardiovascular Medicine, 2022)
Background Proximal protection devices, such as the Mo.Ma system provides better neurological outcomes than the distal filter system in the carotid artery stenting (CAS) procedure. This study firstly evaluated the safety and efficacy of the Mo.Ma system during CAS in a single tertiary referral hospital from Taiwan. Methods A total of 294 patients with carotid artery stenosis who underwent the CAS procedure were retrospectively included and divided into two groups: 152 patients in the distal filter system and 142 patients in the Mo.Ma system. The outcomes of interest were compared between the two groups. The factors contributing to occlusion intolerance (OI) in the Mo.Ma system were evaluated. Results The procedure success rates were more than 98% in both groups. No major stroke occurred in this study. The minor stroke rates were 2.8% (4/142) and 4.6% (7/152) in the Mo.Ma system and filter system, respectively (p=0.419). Patients with hypoalbuminemia significantly predicted the risk of stroke with an odds ratio of 0.08 [95% confidence interval (CI), 0.01-0.68, p = 0.020] per 1 g/d of serum albumin in the filter group. A total of 12 patients developed OI in the Mo.Ma system (12/142, 8%). Low occlusion pressure predicted the occurrence of OI in Mo.Ma group with the hazard ratios of 0.88 (95% CI: 0.82-0.96) and 0.90 (95% CI: 0.84-0.98) per 1 mmHg of occlusion systolic pressure (OSP) and diastolic pressure (ODP), respectively. We further indicated that patients with an OSP of ≥60 mmHg or an ODP of ≥44 mmHg could tolerate the procedure of occlusion time up to 400 seconds, while patients with an OSP of <49 mmHg or an ODP of <34 mmHg should undergo the procedure of occlusion time less than 300 seconds to prevent the occurrence of OI. Conclusion We have demonstrated the safety and effectiveness of the Mo.Ma system during CAS in an Asia population. By reducing occlusion time, our study indicated a lower risk of OI in the Mo.Ma system and proposed the optimal occlusion time according to occlusion pressure to prevent OI during the CAS procedure. Further large-scale, prospective studies are needed to verify our results.